Magnesium as a Promoter of Technological Quality in Sugarcane - Garcia, Ariani [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP]; McCray, James Mabry; Nascimento, Carlos Antonio Costa [UNESP]; Martello, Jorge Martinelli [UNESP]; de Siqueira, Gabriela Ferraz [UNESP]; Tarumoto, Miriam Büchler [UNESP] (Springer Nature, 2020)
The aim of the present study was to evaluate the effect of magnesium (Mg2+) supply on the nutritional status and carbohydrate partitioning of sugarcane plants. The treatments consisted of two Mg2+ levels in nutrient solution (2 mg L−1 and 10 mg L−1). The following parameters were evaluated: leaf chlorophyll content, root morphological parameters, dry matter partition, nutritional composition, partition of carbohydrates, and soluble sugars. All plant growth parameters were influenced by Mg2+ concentrations, except stalk dry matter. Regarding the dry matter apportioning, Mg control plants presented higher dry matter in leaves than those under Mg deficiency. Plants malnourished with Mg presented higher concentration of K+ but not total dry matter accumulation. In addition, photosynthetic pigments production was lowered by Mg deficiency. The concentration of reducing sugars in leaves or roots were not affected by magnesium levels. However, in the stalks, the sucrose concentration was higher in Mg2+ well-nourished plants. Although the dry matter in stalks was not affected by Mg supply, Mg control plants had higher sucrose accumulation in stalks compared to Mg-deficient. Therefore, Mg fertilization seems to be a key to increase sugar yield in sugarcane fields, mainly in those with high K input.
Keywords: Carbohydrate partitioning; Nutrient concentration; Photosynthetic activity; Root development; Saccharum spp